2021
DOI: 10.1159/000512763
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Attenuates Withdrawal and Reduces Craving: A Randomized Controlled Trial in Alcohol-Dependent Patients

Abstract: <b><i>Introduction:</i></b> Preclinical studies have shown that calcium seems to be the active component of the anti-craving drug acamprosate (Ca<sup>2+</sup> bis-acetyl-homotaurinate). Clinical effects in humans have also indicated an association between increased calcium plasma concentration due to acamprosate treatment and better outcome relating to time to relapse and cumulative abstinence. In contrast, low calcium concentration in alcohol-dependent patients was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Furthermore, acamprosate has failed to produce a signi cant reduction in time to rst heavy drinking day in several human trials [29][30][31] raising the question of whether a decline of e cacy is also seen in some human populations. Given the present in vivo microdialysis results of the enhanced effects following co-administration of calcium and sodium acamprosate in rats, and the recently observed positive association between craving and calcium plasma concentrations in human studies 32,33 , the main question of the current voluntary ethanol consumption study was if sodium acamprosate would add on to the effect of calcium with regards to reducing ethanol intake. In concurrence with the results in the microdialysis study, the combined administration of calcium and sodium acamprosate demonstrated potentiated effects and signi cantly reduced the ethanol intake during the whole treatment period, as compared to vehicle treated controls.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, acamprosate has failed to produce a signi cant reduction in time to rst heavy drinking day in several human trials [29][30][31] raising the question of whether a decline of e cacy is also seen in some human populations. Given the present in vivo microdialysis results of the enhanced effects following co-administration of calcium and sodium acamprosate in rats, and the recently observed positive association between craving and calcium plasma concentrations in human studies 32,33 , the main question of the current voluntary ethanol consumption study was if sodium acamprosate would add on to the effect of calcium with regards to reducing ethanol intake. In concurrence with the results in the microdialysis study, the combined administration of calcium and sodium acamprosate demonstrated potentiated effects and signi cantly reduced the ethanol intake during the whole treatment period, as compared to vehicle treated controls.…”
Section: Discussionmentioning
confidence: 86%
“…However, ethanol is known to temporarily lower plasma calcium concentrations in a dose-dependent manner by decreasing secretion of parathyroid hormone and accelerating calcium excretion into the urine [35][36][37] . The effect of calcium treatment has been investigated and showed that increased calcium concentrations in alcohol-dependent individuals was associated with attenuation in the intensity of alcohol withdrawal symptoms 33 . Elevated plasma calcium levels also correlated with decreased alcohol craving in dependent patients undergoing detoxi cation treatment 32 .…”
Section: Discussionmentioning
confidence: 99%